Colonic malakoplakia in a dual stem cell and cardiac transplant recipient: A case report and literature review. Issue 2 (22nd October 2020) - Meredith, Thomas; Dharan, Nila; Killen, Louise; Anandabaskaran, Sulak; Kim, Andrew; Yang, Tao; Marriott, Deborah; Hayward, Christopher; Macdonald, Peter
Abstract: We describe the first published case of malakoplakia in a dual stem cell and cardiac transplant recipient. In the 2 months following cardiac transplantation, our patient developed persistent diarrhea and recurrent E coli bacteremia. Biopsies obtained from areas of colonic thickening revealed malakoplakia. Despite improvement in symptoms with prolonged antimicrobial therapy and reduction of his immunosuppression, he eventually died from sepsis. Our case highlights not only the importance of the timely diagnosis of this rare disorder, but also the difficulty in determining optimal treatment duration, particularly where excision of involved areas is not possible, as data on this disease are lacking. Here we describe our case and review the available literature published on malakoplakia in the cardiac transplant population.